Analysis Of Physical And Chemical Parameters Of Citarum River Water Quality In Karawang Regency: Analisis Parameter Fisika Dan Kimia Kualitas Air Sungai Citarum Di Kabupaten Karawang - Varrel Adha Putra Sentono; Kania Ratnawati; Zalfa Alya Najibah (Media Ilmiah Teknik Lingkungan (MITL), 2026)
In industrialized era, river pollution has become a significant concern. This is due to the disposal of waste into the river and the resulting pollution of the Citarum River, which has a significant negative impact on aquatic life and the activities of communities that use its water. Water quality identify as the conformity of water quality to the river class as outlined in Government Regulation Number 22 from 2021 regarding the execution of environmental safeguarding and administration. This research was conducted to assess the water quality of the Citarum River by examining several parameters: TDS, TSS, pH, BOD, COD, DO, Nitrate, and Phosphate. The research was conducted on January 29, 2021, for 12 times. This research was conducted in the Citarum River around Karawang Regency, with five sampling points divided into five stations. The sampling results, based on the test parameters, indicated that the pollution of the Citarum River requires better management measures to improve its water quality. Efforts to reduce industrial waste and unsustainable agricultural practices are essential to maintain the cleanliness of the Citarum River and maintain environmental sustainability.